PERAN RELATIONSHIP MARKETING-ORIENTED PROMOTION PADA LOYALITAS PELANGGAN - CHANDRA, DANIEL ADRIAN RIZHALDY (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
The tight of business rivalry between the companies caused the cost that must be spent by a company to get the new customers become larger several times much more than cost to keep the existing customers. Therefore, the companies should create a good relationship with their customers to keep them. In order to keep their customers, the trend of marketing concept which originally transactional marketing, now it turns into relationship marketing which explains that the relationship between the company and their customers are no longer based on a short-term relationship or just a single transaction, but this value has been shifted to the further value (it is a close relationship), when the customers becomes the main focus of the company. Economic experts said, that corporate strategies such as promotional programs which focusing on the company's relationship with their customers is very important for the companies to get the attention from their customers. Relationship marketing-oriented promotion strategy is a promotional strategy by the company that is used to realize the relationship marketing in order to build the long-term relationships with their customers to create customer loyalty.